Optimalisasi Jangka Menengah PLTA Memperhatikan Ketersediaan Air Menggunakan Linear Programming - Winasis; Hari Prasetijo; Giri Angga Setia (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
Hydro power plant is kind of electric power generation which utilize energy from water fall to produce electricity. One of its operational problem is limited water supply and available water which can be stored in reservoir. This limitation will affect the electrical energy can be generated by the hydro power plant. This paper present a methodology of medium term optimization of hydro power plant operation to maximize its energy production with considering water availability in reservoir as operational constraint. Operation optimization problem is formulated in Linear Programming model and then solved using Tomlab optimization software. Simulations using water flow data of Ketenger Hydro Power Plant on June 2013 show that this method can be used to solve hydro power plant operation optimization problem well. Based on the simulation results with a period of 720 hours (1 month) the total electrical energy that can be generated is equal to 2990.8 MWh. This value is 69,6 MWh (or 2,3%) greater when compared to the real condition of electrical power generated in June with ammount of 2921,2 MWh.